PENGARUH SELF CONTROL TERHADAP PERILAKU AGRESIVITAS VERBAL DI SMP NEGERI 30 MUARO JAMBI - Husna, Nurul; Ferdiansyah, Muhammad; Yusra, Affan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The influence of self-control on verbal aggressive behavior among seventh and eighth grade students at SMP Negeri 30 Muaro Jambi.This research was conducted at SMP Negeri 30 Muaro Jambi. The data were collected through the distribution of self-control and verbal aggressive behavior questionnaires to seventh and eighth grade students as research respondents. The collected data were analyzed using descriptive statistics and simple regression analysis to determine the magnitude of the influence of self-control on students’ verbal aggressive behavior.The results showed that the level of self-control among seventh and eighth grade students at SMP Negeri 30 Muaro Jambi reached 35% and was categorized as low. This indicates that most students still experience difficulties in controlling their behavior, regulating their thoughts, and considering the decisions they make in various situations. Meanwhile, the level of students’ verbal aggressive behavior reached 73% and was categorized as high. These behaviors include direct active verbal aggression, direct passive verbal aggression, indirect active verbal aggression, and indirect passive verbal aggression.The statistical analysis revealed that self-control had a significant effect on students’ verbal aggressive behavior. The magnitude of this effect was indicated by an R Square value of 0.735 or 73.5%, while the remaining 26.5% was influenced by other factors not examined in this study. The regression equation obtained was Ŷ = 11.405 + (-0.379)X, indicating a negative relationship between self-control and verbal aggressive behavior. This means that every increase in self-control is followed by a decrease in verbal aggressive behavior. Conversely, the lower the students’ self-control, the higher their tendency to engage in verbal aggressive behavior.Based on the findings, it is recommended that schools, particularly guidance and counseling teachers, provide services aimed at improving students’ self-control in order to minimize verbal aggressive behavior. In addition, students are expected to develop better self-control skills in their daily lives to create a more conducive and harmonious school environment.